The Impact of Creative Abilities on Strategic Agility Case Study: Algeria Telecom Company - BOUZID, Alaeddine; BELDJAZIA, Omar (Finance and Business Economies Review, 2022)
This study aimed to determine the impact of creative capabilities on Strategic Agility of the Algerian Telecom Company. To achieve the objectives of the study, 56 questionnaires were distributed to the study sample The study reached several results, the most important of which are: There is a statistically significant effect at the significance level (α < 0.05) for creative abilities in the impact of strategic agility in the Algerian Telecom Company